Flow Regime Transition in the Post-CHF Flow Regimes under Subcooled and Low-quality Conditions. (March 2021) - Liu, Qingqing; Kelly, Joseph; Sun, Xiaodong
Highlights: Weber number is calculated in the IAFB regime; Parametric effects of the inlet subcooling, mass flux, and system pressure on the critical Weber number are studied; A correlation for the critical Weber number is proposed to predict flow regime transition from the IAFB to ISFB/AIAFB regimes; The critical Weber number criterion is validated by the wall convective heat transfer coefficient. Abstract: Post critical heat flux (post-CHF) heat transfer may occur during loss of coolant accidents (LOCAs) in water-cooled nuclear reactors when makeup water quenches the uncovered portion of fuel rods in the reactor cores. Post-CHF flow regimes include inverted annular film boiling (IAFB), dispersed flow film boiling (DFFB), and a transition regime between these two, i.e., inverted slug film boiling (ISFB) for low mass fluxes or agitated inverted annular film boiling (AIAFB) for high mass fluxes. Flow regime transition is important for modeling heat transfer characteristics in the post-CHF flow regimes. Breakup of the liquid core in the IAFB regime represents the flow regime transition from the IAFB to ISFB/AIAFB regimes. This paper first presents a literature review of previous experimental and theoretical studies of the mechanisms of breakup of the liquid core in the IAFB regime and flow regime transition in the post-CHF regimes. To physically explain the breakup of the liquid core in the IAFB regime, the Weber number is calculated from the experimental data obtained from steady-state post-CHF experiments at subcooled and low-quality conditions and a critical Weber number is obtained to describe the flow regime transition from the IAFB to ISFB/AIAFB regimes. Parametric effects of the inlet subcooling, mass flux, and system pressure on the critical Weber number are then studied, based on which a new correlation for the critical Weber number is proposed to predict the flow regime transition from the IAFB to ISFB/AIAFB regimes. Due to the different flow patterns in the transition regime, i.e., ISFB and AIAFB respectively for low and high mass fluxes, the heat transfer characteristics show different trends. The indication of the flow regime transition from the IAFB to ISFB/AIAFB regimes by the critical Weber number criterion matches well with the trend of the wall heat transfer coefficient.